Prevalence of periodontitis and alveolar bone loss in a patient population at Harvard School of Dental Medicine - Mohammad F. Helmi; Hui Huang; J. Max Goodson; Hatice Hasturk; Mary Tavares; Zuhair S. Natto (BMC, 2019)
Abstract Background Although several studies assessed the prevalence of alveolar bone loss, the association with several risk factors has not been fully investigated. The aim of this article is to measure the prevalence of periodontitis by calculating the mean alveolar bone loss/level of posterior teeth using bitewing radiographs among the patients enrolled in the clinics at Harvard School of Dental Medicine and address risk factors associated with the disease. Methods One thousand one hundred thirty-one patients were selected for radiographic analysis to calculate the mean alveolar bone loss/level by measuring the distance between the cementoenamel junction and the alveolar bone crest on the mesial and distal surfaces of posterior teeth. Linear regression with Multi-level mixed-effect model was used for statistical analysis adjusting for age, sex, race, median household income, and other variables. Results Mean alveolar bone level of the whole sample was 1.30 mm (±0.006). Overall periodontitis prevalence for the sample was 55.5% (±1.4%). Moderate periodontitis prevalence was 20.7% (±1.2%), while 2.8% (±0.5%) of the whole sample had severe periodontitis. Adjusted mean alveolar bone loss was higher in older age groups, males, Asian race group, ever smokers, and patients with low median household income. Conclusion The effect of high household income on the amount of bone loss can be powerful to the degree that high household income can influence outcomes even for individuals who had higher risks of developing the disease. Public health professionals and clinicians need to collaborate with policy makers to achieve and sustain high quality of healthcare for everyone.